ANALISIS KARAKTERISTIK FISIK MATERIAL AGREGAT KASAR (SPLIT 2–3 WATURAPA) DAN AGREGAT HALUS (PASIR EX. RORAYA) KABUPATEN KONAWE SELATAN - Saharudin; Romy Suryaningrat Edwin; La Ode Muhamad Nurrakhmad Arsyad; La One; Asrullah Tondasi (Jurnal Teknik Sipil dan Arsitektur, 2026)
Concrete represents a composite material used in construction, made up of aggregates and binders. Aggregates are divided into fine and coarse categories, with cement serving as the key binder. These aggregates are combined with cement, water, and additives to create concrete. Coarse aggregates are vital for the final concrete quality, influencing density and strength through particle size and gradation variations. This research explores the physical traits of coarse aggregates (2–3 cm split from Waturapa) and fine aggregates (sand from Roraya), both from South Konawe Regency, Southeast Sulawesi. The goal is to evaluate their physical features for concrete use. Methods involve sieve analysis, specific gravity and water absorption tests, mud content via No. 200 sieve, moisture levels, bulk density, and Los Angeles abrasion. Results for coarse aggregates indicate standard-compliant sieve analysis, specific gravity of 2.39, mud content 0.52%, moisture 3.25%, bulk density 1.26 g/cm³, fineness modulus 8.93, absorption 1.13%, and abrasion 31.74%. Fine aggregates show medium zone sieve analysis, specific gravity 2.55, mud content 1.06%, moisture 1.38%, bulk density 1.76 g/cm³, fineness modulus 4.20, and absorption 1.13%. Both meet Indonesian National Standards, with coarse aggregates providing rough texture for strength and fine ones ensuring good gradation for workability. This underscores local materials' role as sustainable construction resources. Keyword: aggregate, characteristics, concrete, abrasion